Achievement Motivation and Self-Efficacy in Measuring Student Adversity Quotient - Astuti, Dwi Puji; Kardiyem, Kardiyem; Nuraini, Siti (FKIP Universitas Lampung, 2023)
This study aims to examine and analyze the effect of achievement motivation on adversity quotient, the effect of self-efficacy on adversity quotient, and the effect of achievement motivation and self-efficacy on adversity quotient in Economic Education students of Semarang State University. This study used a type of quantitative approach. The population in this study is students of the Department of Economic Education, Semarang State University class of 2017-2020, totaling 437 students. The sampling technique in this study used purposive sampling. The method of collecting and collecting data using questionnaire questionnaires of achievement motivation scale, self-efficacy scale, and adversity quotient scale that has been tested for validity and reliability. Data analysis techniques in this study use classical assumption testing models, path analysis and coefficient of determination (R2) tests. The results showed that there was no effect of achievement motivation on the adversity quotient of economic education students, there was an influence of self-efficacy on the adversity quotient of economic education students, and furthermore there was no effect of achievement motivation and self-efficacy on the adversity quotient of economic education students.Keywords: Learning Motivation, Self-Efficacy, Adversity QuotientDOI: http://dx.doi.org/10.23960/E3J/v6i1.42-49